2015
DOI: 10.1185/03007995.2015.1101372
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to NICE guidance on glucagon-like peptide-1 receptor agonists among patients with type 2 diabetes mellitus: an evaluation using the Clinical Practice Research Datalink

Abstract: Adherence to NICE guidance for initiating and continuing GLP-1 receptor agonists is low. However, lack of data on ethnicity (for assessing NICE's BMI criteria) and on contraindications and/or hypersensitivity to other diabetes medication in the treatment pathway have limited our ability to fully assess adherence to GLP-1 prescribing. Further research is warranted to better understand general practitioners' prescribing decisions given the cost of prescribing GLP-1 receptor agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Less than a quarter of patients (22.4%) experienced a beneficial metabolic response according to the six months NICE and CatSalut continuation criteria (HbA1c ≥ 1% reduction with ≥3% weight loss), which is in line with the 25%–34% reported by other studies conducted in primary care [29,30,31,32,33,34,44]. This would argue for an independent assessment of the reduction in weight and glycemia in the decision to continue GLP-1RAs therapy, which is further supported by the results of the multivariate analysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Less than a quarter of patients (22.4%) experienced a beneficial metabolic response according to the six months NICE and CatSalut continuation criteria (HbA1c ≥ 1% reduction with ≥3% weight loss), which is in line with the 25%–34% reported by other studies conducted in primary care [29,30,31,32,33,34,44]. This would argue for an independent assessment of the reduction in weight and glycemia in the decision to continue GLP-1RAs therapy, which is further supported by the results of the multivariate analysis.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, 20.5% of patients who initiated GLP-1RA therapy had a baseline HbA1c value <7%, their BMI was ≤30 kg/m 2 , or were prescribed as monotherapy, which is not in line with our local clinical guideline initiation criteria. This is consistent with audits conducted in the primary care setting, where 20–50% of patients deviated from the HbA1c and BMI NICE recommendations (i.e., initiate as dual/triple therapy, and if HbA1c > 7.5% and BMI > 35 kg/m 2 ) [31,32,33,34]. In particular, 12.3% of our patients were prescribed a GP-1RA despite a good glycemic control, which is in line with a real-world study conducted in Spain reporting that 14% of patients initiating GLP-1RAs had a baseline HbA1c value <7% [35].…”
Section: Discussionsupporting
confidence: 83%
“…In a cross‐sectional study of 363 patients with diabetes at 32 practices in the Netherlands, adherence to national diabetes guidelines was suboptimal (adherence in <70% of patients/practices) for several indicators of care . In a retrospective cohort study in the UK of 7133 new users of a GLP‐1 receptor agonist, only 25% of patients initiated GLP‐1 receptor agonist therapy in accordance with the National Institute for Health and Care Excellence (NICE) guidelines . Among 301 patients with diabetes treated with metformin in Australia, 21–31% received metformin in the presence of contraindications or in excessive dosage relative to guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…10 Another retrospective cohort study in the United Kingdom including 7133 primary care patients with a first prescription for GLP-1 RA (age: 58 years, HbA1c 9.2%, BMI 38.4 kg/m 2 ) revealed that 18% of the patients having dual-therapy with a GLP-1 RA achieved a −1% reduction in HbA1c at 6 months. 16 An Italian study consisting of 481 type 2 diabetes patients (baseline: mean age: 57 years, HbA1c 8.7%, BMI: 37 kg/m 2 ) from 6 outpatient units observed that a 35.9% of the patients had reached an HbA1c <7.0% after 12 months treatment with liraglutide. 11 Findings from these studies of primary care patients were consistent with the present investigation that GLP-1RA as add-on therapy could improve glycemic control among type 2 diabetes patients who had poor glycemic control at baseline.…”
Section: Discussionmentioning
confidence: 99%